2011
DOI: 10.1038/pr.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Maternal preeclampsia and risk of bronchopulmonary dysplasia in preterm infants

Abstract: INTRODUCTION:To better understand whether preeclampsia (Pe) increases the risk of bronchopulmonary dysplasia (BPD). RESULTS: Of 753 infants alive at 36 wks, 138 (18.3%) were exposed to Pe. BPD was not significantly related to exposure to Pe either before (odds ratio (OR) 0.73; 95% confidence interval (cI) 0.50, 1.06) or after adjustment for confounding variables (adjusted OR 1.14; 95% cI 0.71, 1.81). If infants were selected by gestational age alone, there was no association (OR 1.05; 95% cI 0.63, 1.75). In co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 23 publications
4
35
1
2
Order By: Relevance
“…1 Several studies have addressed this issue, but results have often been conflicting. For instance, both mortality and a common complication such as bronchopulmonary dysplasia (BPD) have been found to be higher, 2-6 equal, [7][8][9][10] or lower [11][12][13] in infants born after preeclampsia compared with spontaneous preterm labor. There could be several reasons for these discrepancies, including differences in the populations studied, which often came from a single hospital, classification of antecedents of preterm birth, or adjustments made during the analysis stage.…”
Section: Resultsmentioning
confidence: 99%
“…1 Several studies have addressed this issue, but results have often been conflicting. For instance, both mortality and a common complication such as bronchopulmonary dysplasia (BPD) have been found to be higher, 2-6 equal, [7][8][9][10] or lower [11][12][13] in infants born after preeclampsia compared with spontaneous preterm labor. There could be several reasons for these discrepancies, including differences in the populations studied, which often came from a single hospital, classification of antecedents of preterm birth, or adjustments made during the analysis stage.…”
Section: Resultsmentioning
confidence: 99%
“…In our data, once GA was taken into account, BPD did not appear to be associated with inflammatory causes of delivery but rather with placentation disorders. The effect of preeclampsia on BPD is disputed (7)(8)(9)(10), with a population-based study in Australia and accompanying meta-analysis refuting the association (9), but with two recent single-center studies not included in the meta-analysis (7,10) lending support to the "vascular hypothesis" of BPD. It is known that an array of circulating antiangiogenic factors might play a role in preeclampsia and SGA (24) and could represent the link between abnormal placentation and a pathological development of lung blood vessels (25).…”
Section: Pregnancy Disorders and Neonatal Outcomementioning
confidence: 99%
“…Mortality, e.g., has been found to be higher (2,3), lower (4,5), or equal (6) in preeclampsia as compared with spontaneous preterm labor. The same discrepancies occur for bronchopulmonary dysplasia (BPD) (7)(8)(9)(10).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Some studies found an association with BPD, [21][22][23] but others did not. 10,24,25 Most studies focused on maternal disorders but did not look at fetal consequences of placenta-mediated pregnancy complications.…”
mentioning
confidence: 99%